Moral e religião em Freud - Krindges, Sandra Maria (My University, 2016)
Based on the idea about the place and the importance of religion in human life, and the idea about the existence of an ethical crisis today, this Master’s dissertation in philosophy, Moral and religion in Freud, studies Freud’s criticism of religion and Freud’s proposal on moral. Transformations occurred in the field of religion in post-modernity, in the bosom of traditional institutions such as family and religion, and the decline of the symbolic function of paternal representation of authority are aspects of significant influence in the current scenario, when traditional and verticalized models migrate to horizontalized formats in establishing relationships, bonds, and in transmitting values. Starting from the moral proposal in Freudian psychoanalysis, it is attempted to analyze and establish relationships with today's religious behavior and its possible implications with the current ethical crisis of values of reference and sense. Firstly, by analyzing Freud’s major texts dealing with the subject of religion, namely Obsessive actions and religious practices (1907); Totem and Taboo (1913); Moses and monotheism (1939); The future of an illusion (1927), and Civilization and its Discontents (1930), aspects that point out to Freud’s moral proposal and his criticism to religion are highlighted. Secondly, based on these texts, the understanding of concepts of Freudian moral is deepened, and related to some of the assumptions of moral psychology, such as desire, guilt, and obligatory feelings as triggers of moral action. Based on these assumptions, an analysis is performed on how the father issue is placed in Freudian morality, and how it appears in the ethics in psychoanalysis, as well as some of its contributions to the reading of the ethical crisis today. Thirdly, the subject of religion, its role in the human dimension, and in some aspects of today’s religious scenario is dealt with. In this field of religious phenomenon, religious transit unveils in some of its nuances as a symptomatic behavior resultant from the decline of religion as traditionally inherited, as well as related to the aforementioned ethical crisis. Morality in Freud and ethics in psychoanalysis are therefore seen as relevant contributions to understanding the current scenario of fluctuating cultures that instigate low frustration tolerance. In this perspective of analysis, it is observed that the religious market, in turn, at the same time that presents itself as a possibility for the free religious exercise, is also a resource that is external to the subject, and which not always instigates the subject to self-knowledgement, and to a greater and better awareness of his/her moral and religious values.
Partindo-se da ideia em torno do lugar e da importância da religião na vida humana, como também da existência de uma crise ética na atualidade, a dissertação de Mestrado em Filosofia, Moral e Religião em Freud, estuda a crítica freudiana à religião e a proposta moral em Freud. Toma-se em conta que as transformações ocorridas no campo religioso na pós-modernidade, no seio de instituições tradicionais como a família e a religião, e o declínio da função simbólica da representação paterna de autoridade, são aspectos de significativa influência no cenário atual, quando modelos tradicionais e verticalizados migram para formatos horizontalizados no estabelecimento das relações, dos vínculos e na transmissão de valores. E a partir da proposta moral na psicanálise freudiana, busca-se analisar e estabelecer relações com o comportamento religioso na atualidade e suas possíveis implicações com a crise ética vigente, de valores de referência e de sentido. Em um primeiro momento, na análise dos principais textos freudianos que tratam do tema da religião, a saber: Atos obsessivos e práticas religiosas (1907); Totem e Tabu (1913); Moisés e o Monoteísmo (1939); O futuro de uma ilusão (1927) e O Mal-Estar na Civilização (1930) sublinha-se aspectos que sinalizam sua proposta moral e crítica à religião. No segundo momento, com base nos textos referenciados, aprofundam-se conceitos da moral freudiana, relacionando-os a alguns dos pressupostos da psicologia moral, tais como o desejo, a culpa e os sentimentos de obrigatoriedade como motivadores da ação moral. Em torno de tais pressupostos, analisa-se o modo como está posta a questão paterna na moral freudiana e, a partir dela, a ética na psicanálise, bem como algumas de suas contribuições para a leitura da crise ética na atualidade. No terceiro momento desta proposta de estudos, adentra-se no tema da religião, seu papel na dimensão humana e em algumas configurações do cenário religioso da atualidade. Neste campo do fenômeno religioso, o trânsito religioso revela-se, em algumas de suas nuanças, como um comportamento sintomático, decorrente do declínio da religião, como tradicionalmente herdada, bem como relacionado com a crise ética referida. A moral em Freud e a ética na psicanálise são vistas, portanto, como contribuições relevantes na compreensão do cenário atual, de culturas flutuantes que instigam a baixa tolerância à frustração. Nessa perspectiva de análise, observa-se que o mercado religioso, por sua vez, ao mesmo tempo em que se apresenta como a possibilidade do livre exercício religioso, configura-se, também, como um recurso externo ao sujeito, que nem sempre o instiga ao autoconhecimento e a uma maior e melhor consciência de seus valores morais e religiosos.
Keywords: Freud, Sigmund, 1856-1939; Ética; Psicanálise; Religião; Ethics; Psychoanalysis; Religion